2017
DOI: 10.1063/1.4998148
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of subcell depletion layer capacitances in multijunction solar cells

Abstract: A method for measuring subcell capacitance voltage (C–V) in a multijunction solar cell is introduced. The subcell of interest is illuminated by a monochromatic light pulse with a ns rise time. The subcell capacitance is calculated from the measured rise time of the solar cell voltage. The effect of optical coupling is eliminated by introducing a high intensity bias illumination to all subcells below the one measured. The method is verified by comparing the subcell capacitance obtained from four junction solar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…7, bottom inset). The detailed understanding of C-V curves in multijunction solar cells is not straightforward, since only the voltage across the device terminals is known and no information is available about the particular bias at each subcell (Ruiz et al 2010, Rutzinger et al 2017, Hoheisel et al 2011. However, in this case we simply intend to detect the signature of a parasitic diode in reverse bias.…”
Section: Solar Cell Resultsmentioning
confidence: 99%
“…7, bottom inset). The detailed understanding of C-V curves in multijunction solar cells is not straightforward, since only the voltage across the device terminals is known and no information is available about the particular bias at each subcell (Ruiz et al 2010, Rutzinger et al 2017, Hoheisel et al 2011. However, in this case we simply intend to detect the signature of a parasitic diode in reverse bias.…”
Section: Solar Cell Resultsmentioning
confidence: 99%
“…Here, we assume for simplicity time-and intensity-independent values for the capacitance C. In addition, to reproduce the transient V oc under medium light intensities as well as possible, we used a fixed value of 100 nF while the capacitance is typically around 100 nF/cm 2 and depends on the applied voltage and light intensity. 33,41 The LC efficiencies are set to 0.1 for the coupling from both J3-to-J2 and J2-to-J1 (α 32 = α 21 = 0.1) while coupling from J3-to-J1 was set to zero. This is supported by the fact that the coupling efficiency from J3-to-J1 is estimated as α 31 ≈ α 21 × α 32 = 0.01 for the case of α 32 = α 21 = 0.1.…”
Section: A Model Simulation Of Transient V Ocmentioning
confidence: 99%
“…However, in MJSCs, the junctions and admittances of each subcell are electrically (and optically) coupled, so that the response of the MJSC to a change in electrical bias (either modulated or transient) has to be properly analysed in order to separate the contribution of each subcell. Interestingly, while MJSCs have become one of the main target in photovoltaics, only very few studies can be found in the literature that aim at developing methods to separate the admittance (and thus the capacitance) of each subcell from the measurement performed on the MJSC [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%